Pengaruh E-Planning, E-Budgeting, dan E-Procurement Terhadap Sistem Akuntabilitas Kinerja Pemerintah Daerah - Allysa Sekar Apriliani; Novi Dirgantari; Eko Hariyanto; Hardiyanto Wibowo (Owner : Riset dan Jurnal Akuntansi, 2023)
E-Government improves service excellent through making government data and services more available to most people and growing pace, convenience, and more efficient information. Implementation of e-Government, one of which is E-Planning, E-Budgeting, and E-Procurement. This study uses an empirical study on Electronic-Based Government System Data and SAKIP Scores in Regencies and Cities in Central Java in 2018-2020. The purpose of this observed was to determine the effect of E-Planning, E-Budgeting, and E-Procurement on the Government Performance Accountability System (SAKIP) in districts and cities in Central Java. The sampling approach used is saturated sample, in order to obtain 35 data. The research method used is quantitative. The data analysis technique used multiple linear regression analysis. The results showed that E-Planning, E-Budgeting had no effect on the government's performance accountability system (SAKIP) while E-Procurement had a positive effect on the government's performance accountability system (SAKIP).